Interview to the Journal Concept: philosophy, religion, culture. Interviewed by M. A. Khalil - A. V. Smirnov; Mona A. Khalil (Концепт: философия, религия, культура, 2021)
This paper is an interview with Andrey V. Smirnov, Director of the Institute of Philosophy, Russian Academy of Sciences. The interview was dedicated to the broad set of issues that can all be characterized as relative to the umbrella topic of cultural patterns, the indispensability of cultural difference between nations and civilizations and the roots of such phenomena. Expressing the idea of specific mindsets and inherent value orientations, Andrey V. Smirnov adheres to the theoretical approach designed to underline these elements. The panhuman (vsechelovecheskoye) serves for these ends as well as the collective cognitive unconscious. The visions of panhuman oppose to the universalist paradigm (obshechelovecheskoye) and express concern about the drawbacks of cultural unification. Each culture shares one of these two approaches to a certain extent, and the viability of such cultures can be accessed with the view to the interests, goals and projects such cultures or nations nurture. All such phenomena stem from collective cognitive unconscious. Language as its signifier illustrates innate logical structures that also vary: while, for instance, the Arab thought runs on process-based logic that focuses on actions, European one represents substantial logic — that of the existential feeling. In this way all intercultural communication should take others’ visions and adopt to them, which is important not only for translators and interpreters, but also in the political sphere. Advocates of globalism and supranationalism are driven by ideas generated in the West and remain ignorant of the practices that are actually relevant in localities other than the USA or Western Europe. Many examples can be found in the societal shifts that Russia faces. The seemingly non-alternative modernisationalist initiatives that fall within the universalist liberal model are inadequate for the thought style and the corresponding institutional, authority and educational system. The most obvious examples of this deal with the digital sphere, but the cyber transformations as such are not imposing the universalist vision. Rather, it is the underlying culturally-rooted effects of the leverage the United States as the IT leader have and make use of. The questions on how these intercultural communications function now, what form should they take and the very transformations that burden self-sufficient cultures should be analyzed by philosophers. The realities of modern civilizations suggest that those who are set aside in the periphery raise voices and realize national subjectivity.